667 EFFECT OF LEUCINE SUPPLEMENTATION ON PHYSICAL PERFORMANCE, MUSCLE MASS AND QUALITY OF LIFE IN OLDER PEOPLE WITH SARCOPENIA. (8th March 2022) - Witham, M D; Adamson, S; Avenell, A; Band, M M; Donnan, P T; George, J; Hapca, A; Hume, C; Kemp, P; McKenzie, E; Pilvinyte, K; Smith, K; et al.
Abstract: Introduction: Leucine supplementation improves muscle protein synthesis in physiological studies and has been proposed as a treatment to improve muscle mass and physical performance. We tested the effects of leucine supplementation in a randomised controlled trial enrolling patients with sarcopenia. Methods: We conducted a placebo-controlled, parallel group, double-blind, randomised two-by-two factorial trial. Participants aged 70 and over with low muscle mass by bioimpedance and either low grip strength or low walk speed, were recruited from 14 UK sites. Participants were randomised to receive one year of leucine powder 2.5 g three times a day or matching placebo, plus perindopril 4 mg once daily or matching placebo. The primary outcome was the between-group difference in the Short Physical Performance Battery, measured at baseline, 6 and 12 months, analysed using repeated-measures mixed models. Secondary outcomes included grip strength, quadriceps strength, six-minute walk distance, appendicular muscle mass measured by dual x-ray absorptiometry, quality of life measured using the EQ5D tool, falls rates and adverse events. Results: We screened 320 people and randomised 145 participants, mean age 79 (SD 6) years; 78 (54%) were women and the mean SPPB was 7.0 (SD 2.4). 72 were randomised to leucine and 73 to placebo. Median adherence was the same in both groups (76% vs 76%; p < 0.001). Leucine had no significant effect on the primary outcome (adjusted treatment effect 0.1 points [95%CI -1.0 to 1.1]). No significant treatment effect was seen for any secondary outcome. There were similar numbers of adverse events in both groups (leucine 187, placebo 196) and falls rates were similar (leucine 1.9 [95%CI 0.9 to 2.9] per year; placebo 2.9 [95%CI 0.8 to 5.0] per year). Conclusion: Leucine did not improve measures of physical performance, muscle mass or quality of life in older people with sarcopenia.